Au Boulot! First-Year French - Dinneen, David A.; Christiansen, Hope; Kernen, Madeleine; Pensec, Herve (Open textbook library., 1995)
Au boulot! is a two-year college French program consisting of: a textbook, workbook and 21 accompanying audio exercises; as well as a reference grammar, to be used the entire two years. We also insist that our students obtain a full-sized dictionary, and we recommend the HARPER-COLLINS-ROBERT bilingual New Standard Edition. (Instructors will note in reviewing the materials that we provide vocabulary lists at the ends of chapters, with translations, but no glossary. We have become convinced after years of experience that glossaries are counter-productive. It is vital that students learn to use dictionaries, and the sooner the better.)